Search
Ask a question
0

Factor. s^2(t - u) - 9t^2 (t - u)

dont get this one

2 Answers by Expert Tutors

Tutors, sign in to answer this question.
Steve S. | Tutoring in Precalculus, Trig, and Differential CalculusTutoring in Precalculus, Trig, and Diffe...
5.0 5.0 (3 lesson ratings) (3)
0
Heng X. | Everything Math, Science and ChineseEverything Math, Science and Chinese
5.0 5.0 (417 lesson ratings) (417)
0
Corry,
 
the common factor for both are (t-u), we can take it out:
 
(t-u)(s^2-9t^2)
 
And because a^2-b^2=(a+b)(a-b), in this case,
 
 s^2-9t^2
=s^2-(3t)^2   [note: s=a, 3t=b in the above formula]
=(s+3t)(s-3t)
 
So the complete factor for this one is (t-u)(s+3t)(s-3t)
 
Hope it helps.
 
Heng